Methodology of explanation of tactical and technical requirements for means of evacuation of weapons and military equipment - Dachkovskyi , Vоlodymyr (Social Development and Security, 2020)
The main impact force of ground troops  is the hard weapons and military equipment, that is why the loss of one of them is always painful for any army in the world The basic combat weapons and military equipment (high-precision samples of weapons and military equipment) are too expensive to destroy damaged vehicles or leave them on the battlefield. Realizing this, the special vehicles were created for the evacuation of this type of weapons and military equipment – armored repair and evacuation vehicle, which are designed to evacuate from the battlefield damaged and stuck tanks, infantry fighting vehicles, armored personnel carriers, self-propelled artillery system and other units of equipment, even out of the probable enemy fire.Taking into account the analysis of the development of evacuation means which are in the service of the Armed Forces of Ukraine and the armed forces of the leading countries of the world, in this work the method of substantiation of tactical and technical requirements for means of evacuation of damaged weapons and military equipment is proposed. The essence of this method is to distribute the means of evacuation by mass and size, by type of mover, by the method of moving the damaged sample, by the level of application.The formation of requirements is aimed at the transition of evacuation means and basic models of weapons and military equipment to unified basic platforms of the modular type. The implementation of these platforms will make it possible to install various types of special modules of evacuation means (material-handling, load-lifting, etc.) and modules of samples of weapons and special equipment.The application of this metodology will provide an opportunity to obtain technical outlines of evacuation tools for different levels of the hierarchy, taking into account the scope of tasks assigned to them.